2009
DOI: 10.1111/j.1365-2362.2009.02185.x
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acids as metabolic mediators in innate immunity

Abstract: Monocytic activation is differentially regulated by fatty acids and depends on triglyceride levels in T2D. The main finding of the present study shows that eicosapentaenoic acid inhibits the specific binding of LPS to TLR4/MD-2. Eicosapentaenoic acid represents a new anti-inflammatory LPS-antagonist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 21 publications
0
34
0
2
Order By: Relevance
“…12 14 15 However, the exact nature of this interaction is still not quite clear: On the one hand, there is no direct binding of radiolabelled saturated FFA to TLR4 (more specifically, a soluble fusion complex consisting of the FLAG-tagged extracellular part of TLR-4 fused to full-length MD-2 via a flexible linker); 12 on the other hand, the polyunsaturated fatty acid eicosapentaenoic acid blocks LPS binding to an experimental LPS trap. 15 Whether FFA mediate TLR4 activation by inducing its dimerisation is discussed controversially. Lee et al 33 found no effect on TLR4 dimerisation, while Wong et al 34 found that saturated fatty acid induced TLR4 dimerisation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 14 15 However, the exact nature of this interaction is still not quite clear: On the one hand, there is no direct binding of radiolabelled saturated FFA to TLR4 (more specifically, a soluble fusion complex consisting of the FLAG-tagged extracellular part of TLR-4 fused to full-length MD-2 via a flexible linker); 12 on the other hand, the polyunsaturated fatty acid eicosapentaenoic acid blocks LPS binding to an experimental LPS trap. 15 Whether FFA mediate TLR4 activation by inducing its dimerisation is discussed controversially. Lee et al 33 found no effect on TLR4 dimerisation, while Wong et al 34 found that saturated fatty acid induced TLR4 dimerisation.…”
Section: Discussionmentioning
confidence: 99%
“…Serum FFA levels are increased in obese individuals compared with lean individuals, 5 and chronically elevated FFA levels in vivo have been shown to cause various detrimental effects, including impaired insulin sensitivity of muscles 6 and liver, 7 8 endothelial dysfunction, 9 hypertension 10 and increased very low-density lipoprotein production. 11 In addition, FFA affect gene expression of adipocytes, 12 macrophages 13 14 and monocytes 15 in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…S9). Although we and others previously reported some related facts underlying this conclusion, which were observed in a number of different physiological and experimental conditions (12,14,(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33), we would like to emphasize that this study, which focused on AIM, has uniquely linked apparently independent elements to a process that occurs during the progression to obesity.…”
Section: Resultsmentioning
confidence: 95%
“…Thus, it is plausible that an increase in blood AIM may induce vigorous lipolysis in obese adipose tissues, and saturated fatty acids effluxed from adipocytes as a result of lipolysis might activate chemokine production in adipocytes via the stimulation of TLR(s) in a paracrine/autocrine fashion (26)(27)(28). Indeed, palmitic and stearic acids, the major fatty acids comprising triglyceride droplets (29) and well known as stimulators of TLR4 and TLR2 (21,25,30,31), were identified as the components released by adipocytes in response to lipolysis induced by AIM or C75 when the profile of fatty acids in AIM CM and C75 CM was evaluated by gas-chromatography massspectrometry analysis. Consistent with this result, both AIM CM and C75 CM efficiently stimulated the TLR signaling cascade and chemokine production in 3T3-L1 adipocytes, as assessed by degradation of IkBα (Fig.…”
Section: Fatty Acids Effluxed From Adipocytes In Response To Aim-depementioning
confidence: 99%
“…A diferencia de la inflamación aguda o clásica inducida por PAMP, la respuesta asociada con diferentes molécu-las derivadas de un estado metabólico alterado o «DAMP metabólicos» conduce a una inflamación de menor intensidad, mayor duración y sistémica 14 . De esta forma, distintos metabolitos han sido vinculados como generadores de inflamación sistémica de grado bajo a través de su unión a TLR 14 .…”
Section: El Inicio De La Inflamación Sistémica De Grado Bajo Depende unclassified